Isolation and molecular characterization of a novel picornavirus from baitfish in the USA. - Nicholas B D Phelps; Sunil K Mor; Anibal G Armien; William Batts; Andrew E Goodwin; Lacey Hopper; Rebekah McCann; Terry Fei Fan Ng; Corey Puzach; Thomas B Waltzek; Eric Delwart; James Winton; et al. (PLoS ONE)
During both regulatory and routine surveillance sampling of baitfish from the states of Illinois, Minnesota, Montana, and Wisconsin, USA, isolates (n = 20) of a previously unknown picornavirus were obtained from kidney/spleen or entire viscera of fathead minnows (Pimephales promelas) and brassy minnows (Hybognathus hankinsoni). Following the appearance of a diffuse cytopathic effect, examination of cell culture supernatant by negative contrast electron microscopy revealed the presence of small, round virus particles (∼ 30-32 nm), with picornavirus-like morphology. Amplification and sequence analysis of viral RNA identified the agent as a novel member of the Picornaviridae family, tentatively named fathead minnow picornavirus (FHMPV). The full FHMPV genome consisted of 7834 nucleotides. Phylogenetic analysis based on 491 amino acid residues of the 3D gene showed 98.6% to 100% identity among the 20 isolates of FHMPV compared in this study while only 49.5% identity with its nearest neighbor, the bluegill picornavirus (BGPV) isolated from bluegill (Lepomis macrochirus). Based on complete polyprotein analysis, the FHMPV shared 58% (P1), 33% (P2) and 43% (P3) amino acid identities with BGPV and shared less than 40% amino acid identity with all other picornaviruses. Hence, we propose the creation of a new genus (Piscevirus) within the Picornaviridae family. The impact of FHMPV on the health of fish populations is unknown at present.